2015
DOI: 10.1139/cjb-2015-0055
|View full text |Cite
|
Sign up to set email alerts
|

Growth and photosynthesis responses of two co-occurring marsh grasses to inundation and varied nutrients

Abstract: For tidal marshes of the U.S. Northeast, the late twentieth century decline of Spartina patens has been attributed to increased flooding associated with accelerated sea level rise and nitrogen over-enrichment from cultural eutrophication. The objective of this study was to examine the impacts of inundation and nutrient availability on growth, photosynthesis, and interactions of Spartina patens and Distichlis spicata, which co-occur and are common marsh species. Plants were grown in a factorial greenhouse exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…maritima [32]; S . patens , Distichlis spicata , Juncus gerardii [45,46,47]). Under high inundation conditions and when there is low sediment supply, plants need to accumulate enough belowground carbon and build peat to keep up with the increased flooding [9,31,48].…”
Section: Discussionmentioning
confidence: 99%
“…maritima [32]; S . patens , Distichlis spicata , Juncus gerardii [45,46,47]). Under high inundation conditions and when there is low sediment supply, plants need to accumulate enough belowground carbon and build peat to keep up with the increased flooding [9,31,48].…”
Section: Discussionmentioning
confidence: 99%
“…However, Langley et al (2013) used field mesocosms to study inundation, nitrogen and CO 2 effects on a mixed assemblage of S. americanus and S. patens and found that the relative abundance of the species changed along the inundation gradient. Variation in flooding may contribute to a shift in the competitive balance among co-occurring species, as seen in a greenhouse manipulation of inundation and nutrients with Distichlis spicata and S. patens (Watson et al 2015). To better understand how whole marsh assemblages may respond to SLR, other experimental designs such as manipulation of marsh inundation by passive weirs may be useful (Cherry et al 2015).…”
Section: Biomass鈭抜nundation Relationshipsmentioning
confidence: 99%
“…Various inundation鈭抪roductivity relationships have been reported for tidal marsh plants, including parabolic responses (Kirwan & Guntenspergen 2012, Schile et al 2014, Watson et al 2015, linearly declining monotonic relationships (Voss et al 2013), or exponentially declining relationships (Watson et al 2014, Snedden et al 2015. However, research to date has mainly focused on common marsh species found along the Atlantic coast of North America (but see Schile et al 2014 for multi-species biomass data in California, USA).…”
Section: Introductionmentioning
confidence: 99%
“…Aerenchyma is the most prominent feature of Diplachne fusca roots and this increased with increase in salt stress. Aerenchyma is responsible for the efficient exchange of gases throughout the plant (Evans, 2003;Malik et al, 2003;Shimamura et al, 2010;Grigore et al, 2014), and also facilitates bulk movement of salts (Naz et al, 2013;Lynch and Wojciechowski, 2015;Watson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%